2020
DOI: 10.1097/prs.0000000000007024
|View full text |Cite
|
Sign up to set email alerts
|

Abdominoplasty with Scarpa Fascia Preservation: Randomized Controlled Trial with Assessment of Scar Quality and Cutaneous Sensibility

Abstract: Background: Scarpa fascia preservation during abdominoplasty has been shown to reduce complications associated with the traditional technique. As an extension of a previously published randomized controlled trial, this study aims to clarify whether preservation of Scarpa fascia during abdominoplasty has an influence on scar quality or sensibility recovery. Methods: This was a single-center clinical trial, involving 160 patients randomly assigned to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The superficial fascia has received much attention in recent years due to its important role in aesthetic and reconstructive surgery and dermatology [ 1 ]. Indeed, it is a fibroelastic structure inside the subcutaneous tissue that allows for the compartmentalization of the latter in superficial adipose tissue (SAT) and deep adipose tissue (DAT) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The superficial fascia has received much attention in recent years due to its important role in aesthetic and reconstructive surgery and dermatology [ 1 ]. Indeed, it is a fibroelastic structure inside the subcutaneous tissue that allows for the compartmentalization of the latter in superficial adipose tissue (SAT) and deep adipose tissue (DAT) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous surgical approaches have been developed in which its role was highlighted, such as flaps in plastic reconstructive surgery [ 3 , 4 , 5 ] but also in abdominoplasty and liposuction in aesthetic surgery [ 1 ], leading to the need for deeper knowledge of this structure. Odobescu et al, (2021) described a novel method of pre-shaping DIEP hemi-abdominal flaps with the use of a one-step purse-string suture around the periphery of the flap, at the level of the Scarpa fascia (the superficial fascia of the abdomen), improving the projection of the flap and not putting any direct tension on the underside of the flap [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…connective tissue layer of the anterior abdominal wall that divides the hypodermis into two distinct layers: the superficial adipose tissue (SAT) and the deep adipose tissue (DAT). Numerous surgical approaches have been developed using superficial fascia as flaps during plastic reconstructive surgery (Koshima et al, 1996); it has also been used as a dissection guide during superficial lymphadenectomy (Das et al, 2022) and abdominoplasty/ liposuction procedures (Novais et al, 2020). Novais et al (2020) recently reported that those abdominoplasty procedures during which Scarpa's fascia is preserved are characterized by beneficial effects in terms of scar quality and cutaneous sensibility with respect to other techniques.…”
mentioning
confidence: 99%
“…Reported benefits included a reduced drainage volume, time to drain removal, hospital stay, and seroma rate. Another interesting advantage of the supra Scarpa plane of dissection was reported by Novais et al, [26] they demonstrated better regain of supraumbilical sensation after abdominoplasty with supra Scarpa dissection plane in the infraumbilical region.…”
Section: Discussionmentioning
confidence: 80%